2006
DOI: 10.1037/0012-1649.42.3.395
|View full text |Cite
|
Sign up to set email alerts
|

Connecting developmental constructions to the internet: Identity presentation and sexual exploration in online teen chat rooms.

Abstract: The authors examined the online construction of identity and sexuality in a large sample of conversations from monitored and unmonitored teen chat rooms. More than half of the 583 participants (identified by a distinct screen name) communicated identity information, most frequently gender. In this way, participants compensated for the text-based chat environment by providing information about themselves that would be visible and obvious in face-to-face communication. Sexual themes constituted 5% of all utteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
285
2
14

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(325 citation statements)
references
References 35 publications
24
285
2
14
Order By: Relevance
“…Research in developmental psychology has demonstrated that as Internet becomes a main social environment for most people, it becomes an essential arena for identity experimentation and exploration, playing an important role in adolescent development [13]. Same theories are also applicable to Arab youth.…”
Section: How Do People Perceive Themselves In Facebook?mentioning
confidence: 99%
“…Research in developmental psychology has demonstrated that as Internet becomes a main social environment for most people, it becomes an essential arena for identity experimentation and exploration, playing an important role in adolescent development [13]. Same theories are also applicable to Arab youth.…”
Section: How Do People Perceive Themselves In Facebook?mentioning
confidence: 99%
“…A growing body of research indicates that adolescents consider online communication to be a central part of their everyday social lives, and it is used both to acquire new as well as to retain current social relationships (Subrahmanyam et al, 2006;Wolak et al, 2003). The social compensation hypothesis states that some people communicate online because establishing relationships with others is more difficult face-to-face compared to online, due to for example greater anonymity or less perceived social risk (Schneider & Amichai-Hamburger, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Online communication, defined as the frequency, intensity, and rate with which adolescents use the Internet for communicating with others, seems highly important in adolescents' everyday social lives, and they use it to form new as well as to maintain current relationships (Subrahmanyam, Smahel, & Greenfield, 2006;Wolak, Mitchell, & Finkelhor, 2003). Online communication is a multidimensional concept, however, and one way of understanding it is distinguishing between communication that may or may not require an immediate response, regardless of platform.…”
Section: Introductionmentioning
confidence: 99%
“…Since the internet can be considered as a very powerful means of expression of the self, many adolescents nowadays reveal personal information, such as age, gender, orientations (Subrahmanyam, Smahel, & Greenfield, 2006). However, the process of identity formation can be unstable and tumultuous and adolescents can shift from one web-based identity to another very rapidly and unpredictably.…”
Section: Adolescents and Information And Communication Technologies (mentioning
confidence: 99%